Muslim Labor: Income and Hours Of Work in West Sumatera - Ramadhan Razali (Institute of Computer Science (IOCS), 2021)
The discussion about labor still leaves problems from various points of view, especially in economics and religion. The religious environment has a big role in influencing individual behavior in making decisions to work. By using the theory of job supply, the research looks at the impact of income, gender, education, age, and marital status on working hours for Muslim workers. This study uses secondary data from IFLS-5 using the median quantile regression model, this is due to the occurrence of heteroscedasticity. In this article, the researcher emphasizes Muslim workers in West Sumatra Province, which is known as one of the provinces in Indonesia that still prioritizes sharia in the philosophy of life of its people. The results of this study indicate that the average working hours of Muslim workers in West Sumatra is 128 hours per month or 32 hours per week. In addition, the findings of this study report that income and gender have a positive and significant effect on working hours, while age and marital status have a significant and negative effect.